Prader-Willie Syndrome in the Practice of Pediatrician. Modern Approaches to the Diagnosis and Treatment - T.M. Khimenko; A.O. Adakhovska (Zaslavsky O.Yu., 2015)
Objective. To familiarize the doctors with diagnostic criteria and modern comprehensive approach to the treatment of children with Prader-Willie syndrome. The problems of treatment with growth hormone, social integration of patients were stressed, a clinical case from practice is presented. The analysis of the scientific literature of leading foreign and domestic authors has been carried out. The article presents the current approaches to early diagnosis based on large and small diagnostic criteria already at the first months of life, indications for molecular-genetic testing by fish-method to detect microdeletions of chromosome 15. A case of Prader-Willi syndrome demonstrates the typical clinical manifestations, the need for a multidisciplinary approach and continuous monitoring of patients. Conclusions. Prader-Willi syndrome has characteristic features that can be detected in most patients during the first six months of life, which will made it possible to carry out timely correction of metabolic and hormonal disorders and to improve quality of life. To clarify the diagnosis, genetic testing, which today became available in most regions of Ukraine, is successfully performed. The question of supporting hormone therapy that enables to adjust significantly the phenotype of patients with Prader-Willi syndrome, providing adequate physical development, is still open. Long-term use of recombinant growth hormone can prevent a number of complications characteristic of the syndrome, and to improve the quality of life for patients in the future.